A meta ethnographical review of the barriers which children and young adults from ethnic minority backgrounds face when seeking help for self-harm in the UK - Joseph Dalloz (Discover Psychology)
Abstract Objectives Self-harm among UK children from ethnic minority backgrounds is rising. This review, which takes a meta-ethnographic approach, aims to identify barriers to help-seeking in these groups, synthesising the current qualitative evidence in this field. Design Screening identified 5 papers meeting inclusion criteria, which together underwent reciprocal analysis and line of argument synthesis. Results Findings revealed three key themes that reduced help-seeking within these groups: (1) the stigmatisation of self-harm, (2) an upbringing which undervalues disclosure, and (3) a misunderstanding of support services. These acted through one of three main pathways: (1) children not wanting help, (2) children wanting help but being unsure of how to access it, and (3) children getting help but not effectively engaging with it. Conclusion This paper presents a matrix framework through which the barriers to help-seeking for UK minority ethnic groups can be viewed. While effectively synthesising the views of the identified papers, these findings are based on a small number of studies, and thus certain elements may require further development.